The effect of microgravity on the human venous system and blood coagulation: a systematic review. Issue 5 (25th March 2021) - Kim, David S.; Vaquer, Sergi; Mazzolai, Lucia; Roberts, Lara N.; Pavela, James; Watanabe, Manabu; Weerts, Guillaume; Green, David A.
Abstract : New Findings: What is the central question of this study? Recently, an internal jugular venous thrombus was identified during spaceflight: does microgravity induce venous and/or coagulation pathophysiology, and thus an increased risk of venous thromboembolism (VTE)? What is the main finding and its importance? Whilst data are limited, this systematic review suggests that microgravity and its analogues may induce an enhanced coagulation state due to venous changes most prominent in the cephalad venous system, as a consequence of changes in venous flow, distension, pressures, endothelial damage and possibly hypercoagulability in microgravity and its analogues. However, whether such changes precipitate an increased VTE risk in spaceflight remains to be determined. Abstract: Recently, an internal jugular venous thrombus was identified during spaceflight, but whether microgravity induces venous and/or coagulation pathophysiology, and thus, an increased risk of venous thromboembolism (VTE) is unclear. Therefore, a systematic (Cochrane compliant) review was performed of venous system or coagulation parameters in actual spaceflight (microgravity) or ground‐based analogues in PubMed, MEDLINE, Ovid EMBASE, Cochrane Library, European Space Agency, National Aeronautics and Space Administration, and Deutsches Zentrum für Luft‐und Raumfahrt databases. Seven‐hundred and eight articles were retrieved, of which 26 were included for evaluation with 21 evaluating venous, and five coagulation parameters. Nine articles contained spaceflight data, whereas the rest reported ground‐based analogue data. There is substantial variability in study design, objectives and outcomes. Yet, data suggested cephalad venous system dilatation, increased venous pressures and decreased/reversed flow in microgravity. Increased fibrinogen levels, presence of thrombin generation markers and endothelial damage were also reported. Limited human venous and coagulation system data exist in spaceflight, or its analogues. Nevertheless, data suggest spaceflight may induce an enhanced coagulation state in the cephalad venous system, as a consequence of changes in venous flow, distension, pressures, endothelial damage and possibly hypercoagulability. Whether such changes precipitate an increased VTE risk in spaceflight remains to be determined. Abstract :